Pengaruh Inflasi Dan Tingkat Suku Sbi Terhadap Harga Saham Pada Perusahaan Manufaktur Sub Sektor Food and Beverarge yang Go Public Di Bursa Efek Indonesia - Mayasari, Veny (Jurusan Akuntansi Politeknik Negeri Padang, 2019)
The purpose of this research are to determine and analyse the influence of Inflation and SBI rate to Stock Price at Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange.The population used in this research are all Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange. The sampling technique is a census, so the sample size used was the entire population that 10 Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange. Method used in this research is quantitative research. According to the result of regression analysis find that:inflation have significance effects to Stock Price at Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange, SBI Rate have significance effects to Stock Price at Food and Beverage Manufacturing Company that go public in Indonesia Stock Exchange. (3) Inflation, SBI Rate have significance effects to Stock Price at Food and Beverage Manufacturing Company that go public In Indonesia Stock Exchange